2003
DOI: 10.1002/etc.5620220320
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorooctane sulfonic acid in bib (Trisopterus luscus) and plaice (Pleuronectes platessa) from the Western Scheldt and the Belgian North Sea: Distribution and biochemical effects

Abstract: A biomonitoring campaign was conducted in the Belgian North Sea and in the Western Scheldt (The Netherlands) with the primary goal to assess perfluorooctane sulfonic acid (PFOS) contamination and distribution in different biota. This study covers the results obtained for bib (Trisopterus luscus) and plaice (Pleuronectes platessa) and includes the assessment of some stress-related biochemical endpoints. Analysis of liver and muscle PFOS concentrations of both species provided evidence for the existence of a PFO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 33 publications
4
31
0
Order By: Relevance
“…Perfluorooctane sulfonate (PFOS) is a ubiquitous perfluorinated compound with a variety of uses in both industrial and consumer products, leading to its increased global exposure123. It can now be detected in the liver and blood of fish, birds and mammals, even in human serum and milk2456.…”
mentioning
confidence: 99%
“…Perfluorooctane sulfonate (PFOS) is a ubiquitous perfluorinated compound with a variety of uses in both industrial and consumer products, leading to its increased global exposure123. It can now be detected in the liver and blood of fish, birds and mammals, even in human serum and milk2456.…”
mentioning
confidence: 99%
“…For a long time, these fluorinated chemicals were considered metabolically inert and nontoxic (Sargent and Seffl 1970). However, environmental monitoring has shown that degradation to persistent molecules does happen on a large scale, as deduced from the worldwide distribution of compounds such as perfluorooctane sulfonate (PFOS), perfluorooctanoic acid (PFOA), perfluorohexanesulfonate, and perfluorooctanesulfonamide (Dimitrov et al 2004; Dinglasan et al 2004; Giesy et al 2001; Hoff et al 2003a, 2003b; Martin et al 2004). Martin et al (2004), for instance, describe fluorotelomer alcohols as potential sources of perfluorinated acids in regions as remote as the Arctic.…”
mentioning
confidence: 99%
“…PFOS measured in sea otter livers ) and grey seal livers (Kannan et al 2002b ) showed signifi cantly higher concentrations of PFOS in the male liver samples compared with the female samples. In contrast, female porpoise livers from the North Sea showed signifi cantly higher mean concentrations of PFOS compared to the male porpoises ( Van de Vijver et al 2003 ).…”
Section: Sex and Agementioning
confidence: 89%
“…The highest concentrations of PFOS were reported in liver (Hoff et al 2003 ;Moody et al 2001 ;Taniyasu et al 2003 ), muscle (Delinsky et al 2010 ), or whole body (Ye et al 2008b ) of the studied fi sh. When the muscle of sardines and anchovies were analyzed for PFAAs in a study by Fernandez-Sanjuan et al ( 2010 ), no detectable levels of PFAAs were measured, but when whole body fi sh were analyzed, PFOS was found.…”
Section: Fishmentioning
confidence: 90%
See 1 more Smart Citation